The correlation between deformity and metatarsus projection area and the ratios of projection to all metatarsi in direct radiographs in hallux valgus cases (Annals of Medical Research, 2021)
Aim: Hallux valgus (HV) is a common deformity where the hallux deviates laterally in the metatarsophalangeal joint. Although various radiographic measurements have been developed to assess HV, not all are considered universally necessary and the correlations between these methods were not determined. The present study aimed to investigate the correlation between the metatarsus (MT) projection area and the projection rates to all MTs and deformity observed in direct radiographs in HV cases.Material and Methods: We retrospectively analyzed foot radiographs of 100 female cases (20-60 years old). The cases were divided into two groups of 50 HV and 50 non-HV based on HV angles (HVA). HVA>15˚ was accepted as HV. The MT projection areas and the projection rates to all MTs, HVA, and intermetatarsal angle (IMA) were measured in HV cases. Paired t-tests were used to compare continuous numeric variables (Significance: p ≤ 0.05).Results: HVA was higher in HV cases (mean, 22.2˚) when compared to the non-HV group (mean, 7.4˚) (p = 0.000). There was no difference between the mean MT projection areas in HV and non-HV groups. While there was no significant difference between the ratios of the projection area in MT I, II, III and IV to total MT area in HV and non-HV groups, the ratio of the projection area of MT V to the total MT area was lower in HV cases when compared to that of the non-HV group (p = 0.027).Conclusion: Although it was observed that HV did not affect the projection area of each MT, when the total MT area was considered, it was observed that the projection area of MT V was lower. This finding supported that HV is a condition that affects the whole foot.
Keywords: Hallux valgus; metatarsus area; radiography